PENGARUH PENEMPATAN DAN KETERIKATAN KARYAWAN MELALUI MOTIVASI TERHADAP PRESTASI KERJA (Studi kasus terhadap ASN Polda Riau, Pekanbaru) - Fadhil Luthfi; Rosnelly Roesd; Raden Lestari Ganarsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to know the influence of Placement And Employee Attachment Through Motivation To Work Achievement (Case Study Of ASN Polda Riau, Pekanbaru) partially and indirect influence of variable intervening in path analysis. This research takes place in Polda Riau. The number of respondents are 182 ASN, Methods of data analysis using quantitative descriptive method with Path Analysis analysis tool, with the help of SPSS version 21.0. In this study consists of four variables, namely one dependent variable and three independent variables. These variables are Motivation (Y1), Work Achievement (Y2), Placement (X1), and Employee Attachment (X2). The results showed that: 1) Placement variable directly positively influenced significantly to the work performance of ASN Polda Riau, Pekanbaru, 2) Employment Attribute Variables have a significant positive effect on the performance of ASN Polda Riau, Pekanbaru, 3) Placement Variables directly have a significant positive effect on motivation of ASN Polda Riau, Pekanbaru, 4) Employee Attribute Variables directly have a significant positive effect on motivation ASN Polda Riau, Pekanbaru, 5) Motivation variable has no significant effect on job performance, 6) Placement variable has no significant effect on job performance through motivation on ASN Polda Riau, Pekanbaru, 7) Employee engagement variables has no significant effect on job performance through motivation on ASN Polda Riau, Pekanbaru.Keywords : Employee Engagement, Job Performance, Motivation, Placement